TOWARDS BUREAUCRATIZATION: AN ANALYSIS OF COMMON LEGAL REPRESENTATION PRACTICES BEFORE THE INTERNATIONAL CRIMINAL COURT - Hébert-Dolbec, Marie-Laurence (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2015)
The status of victims in the international criminal project since the establishment of the International Criminal Court (ICC) is largely dealt with in the literature. Article 68(3) innovated as it allows victims of mass crimes to present their views and concerns before the first permanent international criminal jurisdiction. Yet, the case law over the last two decades shows that victims will not have the opportunity to directly take part in the ICC proceedings. Those who will participate to the trials are rather their legal representatives. This article explores victim participation through this new actor of international criminal trials. Common legal representation – i.e. the representation of hundreds, or even thousands, of victims by a sole lawyer – was promptly presented as unavoidable. To ensure operational efficiency, the selection of the legal representative was institutionalized. The practice of the Court prompted some impersonal lawyer-clients relationship. The author demonstrates the similarities between the organization of common legal representation in the ICC and the ideal-type of bureaucracy imagined by Weber.